Extra Copies of der(21)t(12;21) plus Deletion of ETV6 Gene due to dic(12;18) in B-Cell Precursor ALL with Poor Outcome - Marina Araújo Fonzar Hernandes; Terezinha de Jesus Marques-Salles; Hasmik Mkrtchyan; Eliane Maria Soares-Ventura; Edinalva Pereira Leite; Maria Tereza Cartaxo Muniz; Maria Teresa Marquim Nogueira Cornélio; Thomas Liehr; Neide Santos; Maria Luiza Macedo Silva (Case Reports in Genetics)
Acute lymphoblastic leukemia (ALL), CD10+ B-cell precursor, represents the most frequent type of childhood ALL from 3 to 6 years of age. The t(12;21)(p13;q22) occurs in 25% of cases of B-cell precursor ALL, it is rare in children less than 24 months and have been related to good prognosis. Some relapse cases and unfavorable prognosis in ALL CD10+ are associated with t(12;21) bearing additional aberrations as extra copies of chromosome 21 and ETV6 gene loss. This report describes the case of a 15 month-year old girl, who displayed a karyotype with addition on chromosome 12p plus trisomy 10 and tetrasomy of chromosome 21. Molecular cytogenetic studies revealed two extra copies of the der(21) t(12;21), trisomy 10 and deletion of the second ETV6 gene due to the dic(12;18). These findings show the great importance of molecular cytogenetic studies to clarify complex karyotypes, to define prognostic, to carry out risk group stratification and to support correctly disease treatment in childhood acute lymphoblastic leukemia.